PROFILE OF INTESTINAL PROTOZOAN PARASITES IN FARMING COMMUNITIES IN GISTING SUBDISTRICT, TANGGAMUS DISTRICT, LAMPUNG PROVINCE - Suwandi, Jhons Fatriyadi; Saftarina, Fitria; Kartika, Juspeni (Fakultas Kedokteran Universitas Sriwijaya, 2025)
Intestinal parasitic infections remain a health problem in communities. Surveys of intestinal protozoan infections in Lampung Province are limited. The transmission of intestinal protozoan infections is generally through the oro-faecal route, which is related to environmental and behavioral factors. Farmers are one of the communities that are potentially infected. Gisting Sub District is one of the agricultural centers in Lampung Province. Farmers' contact with the environment will increase the risk of intestinal protozoan infection. This study aims to determine the Species of intestinal parasites found in farming communities. The design of this study is a descriptive observational survey. Feces collected were examined for parasitological examination at the Parasitology Laboratory, Faculty of Medicine, University of Indonesia. The results showed, the prevalence is 9.33%, consisting of Blastocystis sp. protozoa (6.67%), Entamoeba histolytica/dispar protozoa (1.33%), and a mixture of Blastocystis sp. and Endolimax nana (1.33%) among the research subjects.